Mechanism of Emulsion Formulation and Substances in Maintaining Skin Hydration - Shabrina, Ayunda Myela; Simanjuntak, Aprilia Artha Pratama; Sylvia Nurrasjid2, Evi; Amalia, Eri (Universitas Padjadjaran (Unpad), 2025)
Proper skin hydration is essential for maintaining healthy skin and protecting it from environmental damage. A thorough understanding of the skin’s structure can help researchers identify its layers and components, leading to the development of effective skin hydration formulations. Emulsions are commonly used because they combine water and oil phases, along with ingredients that preserve hydration and enhance chemical penetration through the stratum corneum. Consequently, emulsions are prevalent in skincare and cosmetic products, which are often supplemented with humectants, occlusive agents, and emollients to enhance their efficacy. This study explores the mechanisms through which emulsions support skin hydration, focusing on the roles of water and oil in moisturizing and serving as a skin barrier, as well as the functions of humectants, occlusive agents, and emollients. In conclusion, the stratum corneum is critical for maintaining skin hydration by regulating the water and oil content within its cells and the lipid-rich intercellular spaces. Humectants, occlusive agents, and emollients each enhance hydration through unique mechanisms. We hope this article will assist researchers in developing highly effective, hydrating skincare and cosmetic products.